2016
DOI: 10.1002/cssc.201501392
|View full text |Cite
|
Sign up to set email alerts
|

Hole‐Transporting Materials Based on Twisted Bimesitylenes for Stable Perovskite Solar Cells with High Efficiency

Abstract: A new class of hole-transport materials (HTMs) based on the bimesitylene core designed for mesoporous perovskite solar cells is introduced. Devices fabricated using two of these derivatives yield higher open-circuit voltage values than the commonly used spiro-OMeTAD. Power conversion efficiency (PCE) values of up to 12.11% are obtained in perovskite-based devices using these new HTMs. The stability of the device made using the highest performing HTM (P1) is improved compared with spiro-OMeTAD as evidenced thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The hole‐transporting material Spiro‐OMeTAD has been shown to crystallize over time, and this process is accelerated at higher temperatures, even though the glass transition temperature (125 °C) is well above the operating conditions . Several novel hole transporting materials have been introduced in the last years, of which many show an improved stability of the device under operating conditions, generally achieved by either increasing the glass transition temperature or by cross‐linking the HTM . We further note that the loss in performance is often related to the use of additives like Li‐TFSI, tert ‐butylpyridine ( t BP), and Co‐complexes, necessary to oxidize the HTM and achieve high enough conductivities to ensure balanced charge extraction and maximum device performance .…”
Section: Long‐term Viability: Stability and Sustainabilitymentioning
confidence: 89%
“…The hole‐transporting material Spiro‐OMeTAD has been shown to crystallize over time, and this process is accelerated at higher temperatures, even though the glass transition temperature (125 °C) is well above the operating conditions . Several novel hole transporting materials have been introduced in the last years, of which many show an improved stability of the device under operating conditions, generally achieved by either increasing the glass transition temperature or by cross‐linking the HTM . We further note that the loss in performance is often related to the use of additives like Li‐TFSI, tert ‐butylpyridine ( t BP), and Co‐complexes, necessary to oxidize the HTM and achieve high enough conductivities to ensure balanced charge extraction and maximum device performance .…”
Section: Long‐term Viability: Stability and Sustainabilitymentioning
confidence: 89%
“…As seen from this data, both J sc and FF were slightly lower in comparison with the average parameters of the device using Spiro‐OMeTAD. Many studies have pointed out that the faster hole mobility is responsible for the greater short‐circuit density and higher fill factor of PSC. This coincided with the drift mobility values for V997 and Spiro‐OMeTAD.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have demonstrated that the high ll factor of PSC originates from the fast hole mobility. 38,39 In the previous section, it was mentioned that reorganization energy of the ortho position is higher than that of the para and meta positions, resulting in a negative contribution to the hole mobility of the ortho. However, the two properties of transfer integral and reorganization energy offset each other.…”
Section: Exciton Binding Energies and Charge-transfer Integralsmentioning
confidence: 99%